Study on Glass Fiber/Epoxy Gradient Damping Composites - Zhen, Hong; Xiang, Wang; Xiao-Lin, Xie; Zhi-Peng, Li; Li-Ying, Wan (Asian Journal of Chemistry, 2013)
A kind of composites was prepared by pre-impregnated-hand lay-up process that each glass fabric impregnated by epoxy resin of different damping properties was placed in different layer. The damping properties of composites were studied by dynamic thermomechanical analysis (DMA). The results show that the gradient loss peak in loss factor-temperature spectrum of composites shows this kind of composites have gradient damping effect, which reaches a kind effect of broadening the effective damping temperature range. The effective damping temperature range of glass fabric/epoxy-matrix gradient damping composites reaches 34.5 ºC, the loss factor is 0.516, the glass transition temperature (Tg) is 23.6 ºC, the composites have higher damping properties at 13.2-47.7 ºC. It is more conducive to use the epoxy resin with best damping properties in the middle layer to improve damping properties of composites at room temperature.